Some character theory for groups of linear and antilinear operators - Newmarch, J.O. (AIP Publishing, 1983)
Elementary group concepts are recast into a form applicable to finite magnetic groups of linear and antilinear operators. Analogs of useful definitions for linear groups such as the Frobenius-Schur invariant, commutator subgroups, and ambivalent classes are considered. These are applied to the 180 magnetic single and double point groups and it is shown that only seven require independent treatment of characters.